Exploring influenza vaccination coverage and barriers to influenza vaccine uptake among preschool children in Fuzhou in 2022: a cross-sectional study - Jia, Haimei; Gao, Wenyan; Huang, Xun; Wang, Qinghua; Huang, Yonghan; Chen, Liang; Zheng, Desi; Zhang, Yinchuan; Xu, Lifei (Frontiers in Public Health, 2025)
BackgroundChildren are vulnerable to influenza virus due to their developing immune systems, particularly children aged 6 months-5 years (preschool children). To improve the uptake of influenza vaccine in preschool children, it is important to determine the influencing factors of Chinese parents/guardians’ (P/Gs) intention and behavior for children to receive. We implemented an investigation to determine coverage of influenza vaccination in preschool children and the influencing factors of being vaccinated against influenza among preschool children in Fuzhou.MethodsThis is a cross-sectional study. Using a hierarchical approach, based on the coverage of influenza vaccination in preschool children, the 12 districts/counties in Fuzhou were divided into two levels. In each level, two urban districts and two counties were selected, including 2 randomly selected vaccination clinics and 2 kindergartens. A standardized anonymous questionnaire was used to collect information on P/Gs. Chi-square testing and multivariate logistic regression were used to analyze factors that may be associated with influenza.ResultsThe coverage rate of influenza vaccination was 7.38% among preschool children in 2022 in Fuzhou City. A total of 8,768 guardians completed the questionnaire. 54.70% of the responders had received at least one dose of flu. Only 23.56% of the P/Gs involved were able to correctly list the influenza clinical feature. Higher education status had higher coverage (p-values < 0.05). Multivariate analysis showed birth order [odds ratio (OR) = 0.76, 95% confidence interval (CI): 0.63, 0.92], medical insurance [OR = 1.42, 95% CI: 1.22, 1.65], occupation [OR = 0.84, 95% CI: 0.75, 0.93], average monthly household income ≥ 10,000 [OR = 0.66, 95% CI: 0.56, 0.79], vaccine prices > 200 [OR = 1.66, 95% CI: 1.41, 1.97], and total duration of each vaccination session [OR = 0.49, 95% CI: 0.42, 0.58] were associated with flu vaccination.ConclusionInfluenza vaccination coverage among preschoolers was low, and parental/guardian knowledge regarding influenza prevention was inadequate. Enhanced awareness, vaccine understanding, and recommendation policies correlated with higher coverage. Authorities should implement sustainable financing and incentives to ensure access and affordability, while promoting education to convert vaccination intentions into actual uptake.